Effects of sugarcane expansion on development and land use and land cover change (LULCC) in Brazil: a case study in the state of Goiás - Link, Tyler (Kansas State University, 2015)
As concerns increase over climate change, energy independence, and higher fuel prices, Brazilian sugarcane ethanol is seen as a part of a clean energy future. Brazilian sugarcane ethanol was developed with a long history of government support, and with the introduction of the flex fueled car in 2003, demand rose dramatically. These factors have helped sugarcane expand beyond its traditional regions of Brazil into the Cerrado. More recently however, private capital from both domestic and foreign companies have started investing in Brazilian agriculture and these investments have helped fuel the sugarcane expansion into the Cerrado in the last 15 years. Over 22 sugarcane mills have been constructed in the Brazilian state of Goiás, located in the heart of the Cerrado. The increased investments driving the expansion of sugarcane into the Cerrado brings numerous questions regarding its environmental and social impacts. Thus, the goal of this thesis is to understand how the structural organization of the sugarcane ethanol mills’ affects development at a municipality level in the state of Goiás, Brazil. More specifically, this thesis has two objectives; to evaluate the effects of the sugarcane mills’ influence on land use and land cover change in these municipalities; and to compare how domestic owned mills, foreign owned mills, and jointly owned mills affect socioeconomic development on the municipalities. Three municipalities were analyzed, Edéia, Caçu, and Quirinópolis. Results showed that land use and land cover change varied by municipality. The majority of Edéia’s sugarcane expansion came from lands already in agricultural use. On the other hand, Caçu’s and Quirinópolis’s sugarcane expansion came from pasture lands. However, throughout all the municipalities, sugarcane expansion over native vegetation was small. All three municipalities increased their socioeconomic development levels over the past 20 years as reported on the Human Development Index. In addition, urban survey responses revealed that the residents of Edéia perceived the sugarcane mill had made their lives better than respondents in either Quirinópolis or Caçu. However, this analysis covers only a brief period of time, and future analysis of these, and other municipalities that host sugarcane mills throughout the Cerrado will be needed.
Keywords: Brazil; Sugarcane; Development; Land Use and Land Cover Change (LULCC); Goiás; Cerrado; Geography (0366); Remote Sensing (0799)